Gender Balance in Church Choir and Choir Leadership: A Study of Selected Churches in Ibadan - Akande, Sunday Olufemi (Journal of Gender and Power, 2022)
The struggle for gender equality has been a long and continuous skirmish. The need for gender equality continues to evolve globally and hasn’t left a field of study such as music and an institution; church choir vindicated for a no discourse. The imbalance between men and women in choir is a global issue that has garnered attention from researchers, Music educators, and music directors. Some scholars claimed the gender identity of choir singers has shifted dramatically in the past century, from a male only club into an activity for females. The leadership positions; Music Director, Assistant Music Director, Organist, Welfare Director, Treasurer, Financial Secretary, Librarian, Public Relation Officer, General Secretary etc. though relative from one church choir to another has some gender struggles. The aim of the study was to propose gender balance in the Church Choir and Choir leadership. In doing this, it analyses the ratio of female choristers and male choristers in selected churches in Ibadan and the gender representations on the different leadership positions in the Choir. It also aimed at identifying leadership roles or responsibilities of female and male in the selected choir. It elucidates aptly on biblical acme as it touches Church choir and gender. The study employed a descriptive survey research design and data were collected through observation and interview and analysed with Pie chart and Percentage error. The study concludes that both males and females gender are fit to be a member of the Church choir and can play any leadership role. Church music directors and Choral music educators must celebrate all elements of music; not only encouraging members to engage in musical experiences during adolescence, but also equipping them with the necessary knowledge and skills to find success and lifelong engagement with music.